ANALISIS EFEKTIVITAS METODE PEMBELAJARAN BERBASIS BUKU BERBAHASA ARABDALAM MENGUATKAN WAWASAN KEISLAMAN DI PESANTREN QUR’ANMADRASAH ALIYAH MARKAZ IMAM MALIK MAKASSAR - Munawira S, Siti; Malli, Rusli; Dewanti Palangkey, Rahmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Mastery of classical Arabic literature is a crucial tool for comprehensively deepening Islamic understanding within the pesantren environment. This study aims to analyze the use of Arabic-language textbook-based learning methods, assess their effectiveness in strengthening Islamic understanding, and explore the perceptions of educators and students at the Pesantren Quran Madrasah Aliyah Markaz Imam Malik in Makassar. The research method employed is descriptive qualitative, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The results reveal that instruction is conducted bilingually using standard reference texts such as Silsilah, Nawaqidul Islaam, Shalatsah al-Ushul, Qowaidul al-Arba’a, Mulakhash Kitab Tauhid, Syarhu al-Hadits al-Arba’iin, and Al-Bidayatu fii Ulumil al-Qur’aan through three stages: planning, implementation, and evaluation. The implementation of this method is considered quite effective in broadening the students’ Islamic horizons. It was concluded that there is a very positive perception among educators and students, where the use of this method has a significant impact on improving the understanding of Islamic knowledge and its application in daily life. This study recommends strengthening the Arabic language proficiency of students so that the acceleration of understanding of advanced texts can proceed more optimally.